The Implementation of Animated Film as Media to Teach Writing Narrative Text to the Eighth Grade Students of Junior High School - ZAHROH, FATIMATUS (RETAIN : Journal of Research in English Language Teaching, 2014)
The Implementation of Animated Film as Media to Teach Writing Narrative Text to the Eighth Grade Students of Junior High School Fatimatus Zahroh English Education, Languages and Arts Faculty, State Unuversity of Surabaya Fatim.english@yahoo.com Dosen pembimbing Him’mawan Adi Nugroho, S.Pd., M.Pd English Education, Languages and Arts Faculty, State University of Surabaya Him’mawan_19@yahoo.com Abstrak Menulis adalah salah satu kopetensi dalam bahasa inggris.Bagi murid,Menulis di anggap keahlian yang sangat sulit, karena tidak hanya mengorganisir ide, tetapi menterjemahkan suatu ide pada text sehingga bisa di baca. Animasi film adalah salah satu media yang dapat di gunakan dalam mengajar khususnya Menulis. Tujuan dari studi ini mempunyai tiga rumusan masalah: (1) penerapan animasi film sebagai media pembelajaran narrative text pada kelas delapan SMP N 1 Bangkalan. (2) masalah yang dihadapi oleh guru dalam pembelajaran narrative text engan menggunakan animasi film pada kelas delapan SMP N 1 Bangakalan.(3) respon murid dalam penggunaan animasi film dalam pembelajaran menulis text narrative pada kelas delapan SMP N 1 Bangkalan. Design penelitian ini menggunakan penelitian deskriptif kualitatif. Subject yang di gunakan pada penelitian ini adalah guru dan murid kelas VIIIG SMP N 1 Bangkalan. Adapun instrument yang di gunakan pada penelitian ini, di antaranya menggunakan Checklist, Field note, wawancara dan angket. Hasil dari penerapan animasi film dalam mengajar menulis text narrative di katakan sukses. Hampir seluruh siswa bisa menulis text narrative dengan baik penerapan animasi flm dalam mengajar text narrative mendapatkan positif respon dari murid. Dan permasalahan yang di hadapi oleh guru dalam mengajar narrative text dengan menggunakan animasi film, salah satunya adalah murid merasa kesulitan dalam menangkap maksud dari pembicara pada animasi film tersebut. Kesimpulan, dari penerapan animasi film dalam mengajar text narrative mendapatkan positive respon dari murid. Dengan menggunakan animasi film sebagai media pada pembelajaran menulis narrative text bisa menambah motivasi siswa dan juga antusias dalam pembelajaran text narrative. Dan bisa di simpulkan media yang di gunakan pada pembelajaran text narrative di kelas sangat menarik dan menyenangkan. Kata Kunci: menulis, teks narrative, animasi film Abstract Writing is one of the competences in English. It is considered as the most difficult skill for the students because not only generating and organizing ideas, but also translating these ideas into text which can be read. Animation is kind of media that can be used in teaching writing. The purpose of this study was to describe : (1) the implementation of animated film as a media in teaching writing narrative text to the eight grade student of SMP N 1 Bangkalan.(2) problems are faced by the teacher in teaching writing narrative of using animated film text to the eight grade student of SMP N 1 Bangkalan.(3) the students’ responses toward the use of animated film in teaching writing narrative text to the eight grade students of SMP N 1 Bangkalan This research is a descriptive qualitative research. The subjects are the teacher and the students of VIII G SMP Negeri 1 Bangkalan. The instruments which are used in this research are observation checklist, field note, Interview and questionnaires. The result of the implementation of animated film in teaching writing narrative was successes. Most of students were able to composing a good narrative text. The implementation of animated film gets positives responses from the students. Students are willing to compose a narrative text. For the problem faced by the teacher, by using animated the teacher was the students difficult to catch the native speaker. In conclusion, the implementation of animated film in teaching writing narrative text gets positives responses from the students. By watching animated film as media in teaching writing narrative can gains the students motivation, and also their enthusiasm in teaching learning writing narrative text. It could be concluded that techniques applied in the class were more fun and enjoyable. Key Words : Writing, Narrative text, Animated Film INTRODUCTION Writing is one of the competences in English. It is considered as the most difficult skill for the students. selecting the topic is the important thing that students have to do before they start writing. But the fact, when th students start to write, they get difficulty. In teaching writing, the teacher can use various media. Video film is a kind of media that is usually used in the classroom. According to Stemplesky and Tomalin (1990:6-7) animated film has difference types of purpose, there are : active viewing, vocabulary, grammar, pronunciations, listening and speaking skill, reading and writing skill, cross-cultural concern, and testing. Teaching with video can be exciting. Four or five minutes video tape material can easily provide enough stimulating input for one hour’s teaching, Lonergan (1984:2). Animated films are the ones in which individual drawing, paintings, or illustrating is photographed frame by frame. According to Hornby, (1995:171) animated film is a film made photographing a series of a gradually changing drawing, so they look as if they are moving. Animation videos are often directed by to apply by most children, but easily can be enjoyed by all. It means that by using animated film in teaching writing can bring new atmosphere for the students in teaching and learning process. In junior high school up to senior high school students are obliged to master short functional text such as descriptive text, recount text and also narrative text. Narrative is text which tells a story and entertains or informs the reader or listener (Anderson 1998:8). Narrative usually tells one’s experiences or a short story which states and resolution of problem. In teaching writing nnarrative,The researcher wants to take a research entitled “the implementation of animated film as material to teach narrative text to eight graders student”. According to Harmer (2007, 4-5), There are four step how to teach writing, (1).Planning.Writers plan what they are going to write, before starting to write or type, they Try and decide what it is they are going to say. To make easy, for some writers this may involve making detailed note. When planning, writers have to think about three main issues, the first place they have to consider, the purpose of their writing since this will influence. Not only the type of the text the wish to produce, but also the language they use, and the information they choose to include. The secondly, the writers think of the audience, this will influence not only the shape of the writing, but also the choice of language. For example, it is formal or informal in tone. Thirdly, writers have to consider the content structure of the piece, which means how best to sequence the fact, ideas, or arguments which they have decide to include. (2) Drafting. it can refer to the first version of a piece of writing as a draft. This first ‘go’ at Text is often done on the assumption that it will be amended later. At the writing process proceeds into editing, a number of drafts may be produced on the way the final version. (3)Editing .(Reflecting and Revising) Writers have to produce a draft, they then, usually, read though what they have Written to see where it works and where it does not. Although, the order of information is not clear and also the ambiguous or confusing, they can move paragraph around or write a new introduction and also they may use a different form of words for a particular sentence. Reflection and revising are often helped by other readers who comment and make suggestion. For another reader’s reaction to piece of writing will help the author to make a appropriate revisions. (5)Final Version Writers have edited their draft, making changes they consider to be necessary, They produce their final version. This may look considerably different from both the original plan and the first draft, because things have changed in the editing process. For the writer is now ready to send the written text to it intended audience Those stage in the following by: Planning à drafting à editing à final version Media is one of the ways in teaching new material to the students is to use many kinds of media. Commonly, media can be divided into three types. They are visual media, audio media, and audio visual There are some steps that have to be done in order to reach the successful in teaching writing using video, especially there stages in writing: pre writing, whilst writing, and post writing. (a) Pre writing activities. In pre writing activities, include pre-viewing activity and viewing activity. (b) Pre viewing activities,In pre- viewing activity, the teacher gives information about what will be played, the theme of animated film. The teacher asks to the students to keep silent and also gives command about what students should do during the viewing activity. (c) Viewing activity During the viewing activity, the teacher plays animated film twice. The animated video is about 7 minutes. In this activity students should take a note about the important part in the animated film. (d) Whilst Writing activities,In whilst writing activity is includes the post viewing activity. The students are asked to make summary about way they have watched in the form of narrative composition. (e)Post writing activities.The teacher collects the student work then asks some students to present their work in front of the class. The teacher gives comment orally.In the end of observation, the researcher interviewed the teacher toward the implementation of animated film in teaching writing narrative text. Also the researcher gave some questionnaire toward the responses of students by using animated film. Based on the background above, the research questions are formulated to the following: 1. How is the implementation of animated film as a material in teaching writing narrative text to the eight grade student of SMP N 1 Bangkalan ? 2. What problems are faced by the teacher in teaching writing narrative of using animated film text to the eight grade student of SMP N 1 Bangkalan ? 3. How are the students’ responses toward the use of animated film in teaching writing narrative text to the eight grade students of SMP N 1 Bangkalan? According to research question above, the objectives of study are to: Todescribe the implementation of animated film as a material to teach writing narrative text to the eighth grade student of SMP N 1 Bangkalan. To identify problems faced by teacher in animated film in teaching writing narrative text to the eighth grade student of SMP N1 Bangkalan. Describe the students’ responses toward the use of animated film in teaching writing narrative text to the eighth grade students of SMP N 1 Bangkalan. From this study, the researcher expects that this study will be useful and beneficial for the English teachers by using animated film as a media in writing narrative texts. The finding of this study will give the valuable and useful information for the English teacher in the junior high school as feedback or reflection of their teaching. The teacher can use the information to reflect whether they have achieved the objectives of their teaching or not, so they can improve their teaching media. In addition, the student participation toward the media can become feedback for the teacher whether the media used in the class have already aroused the student interest or not. METHOD The research design in this study is descriptive qualitative. The design is used since this study is aimed to describe the media applied by the teacher in teaching writing narrative. According to Bogdan & Biklen (1992:29-32), a study is categorized as qualitative if the study meets one of the following characteristics. First, the setting and the data are natural. It means that there is no intervention from the researchers so that the events being observed happened as the natural condition. Second, qualitative data are described in the forms of words rather than number. Third, the sample taken is determined purposefully. Fourth, data analysis is one while collecting and interpreting data. The last, a context and meaning is an essential concern to the qualitative approach. It means that the research that uses this approach focuses on how people make sense of their experience. There is no attempt to predict what will happen in the future but rather to understand a unique and particular context. This study is categorized as descriptive qualitative since it met those five characteristics above. In this study, the writer tries to describe, explain, and report the application of animated film to teach writing narrative texts. The subject of the study conducted the students of class VIII of SMP N 1 Bangkalan priode 2013/2014 which consists of 32 students and also their teacher, Ms. Husnul khotimah, S.Pd. it was supposed to learn narrative text for their material in the second semester. The teacher used animated film in teaching writing narrative text. The setting of this study conducted in SMP N 1 Bangkalan. It is located in jalan Trunojoyo no.2, Bangkalan. In SMP N 1 Bangkalan these are first, second and third grades. Meanwhile the researcher chooses the second graders. The setting is chosen based on some consideration. The first consideration is because the location of this school is strategies. The second consideration is because this school was appointed by the government to be national school. Therefore, the school is believed to have a better quality in term of curriculum, teacher, students, facilities, headmaster, officers’ and management of the school. Therefore, English teachers and the students of SMP N 1 Bangkalan will be the sources of data in this study. According to Ary et.al (2006:453), the instruments in qualitative research used by researcher are field notes, interview guides and documentation. In this study to gain the data, the researcher will used checklist, field notes during observation as the primary instrument, students’ writing task, and interview guide and questionnaire sheet. 1. Observation Checklist During the observation, the researcher used the observation checklist to help the collecting data. The research will observe all the activities of writing during teaching learning process. The checklist consisted list of the material used by the teacher when she is explaining the lesson in teaching learning process. The observation checklist is in the form yes or no answer. (see appendix 1) 2. Field Notes According to Ary et.al (2006:477), field notes are the instrument to collect data during the observation. In this study, the field notes become the primary instrumentation since they are used to get data about the kinds of techniques, the procedures or activities in applying them, students’ participation towards the techniques, material and media in the classroom. To gain the data during observation, the researcher writes the events happening in the class. The field notes are used since field notes in qualitative research are brief notes included of all written reports during the observation (Ary et.Al,2006:477). The purpose of applying the daily field note is to make the researcher remembers the facts and details that happened during observation. It is used to observe the implementation of animated film as material to teach writing narrative. 3. Interview Guide This instrument is used to get-depth information from the teachers about the media of teaching writing narrative. The interview guide for the teacher consist of the question that the problem face by the teacher. These questions are based on the indicators of the sub variables with the data. The questions in the interview guide are asked one of the team teachers in the regular class. As stated by Good (1972:238-239), interview can provide many types of information that can only be secured though face-to-face contacts an more complete answers since the interviewer can ask the answer directly. 4. Questionnaire In this research, questionnaire is given to the students to know their response about teaching writing narrative text by using animated film. It would be given at the end of the observation to enable the students to answer all the questions. She asked the students to answer 8 questions in written form. For number one up to number two are about English in writing, For number three up to number five are about narrative text and last for number six up to number are about the implementation of animated film in teaching writing narrative. The data of observation sheet are collected by observing teacher’s and students’ activities when animated film is implemented in the teaching writing in the classroom. The problem faced by the teacher, the researcher used interviewed. And also the last the result of the questionnaires described the students’ responses toward the used of animated film as a material in teaching writing narrative text the research observed the activity during the teaching and learning process in detail. checklist, Field note, interview guide and Questionnaires. In doing the observation, the researcher will enter the classroom and become a passive observer since the beginning of the lesson until the period of the English time ended. A passive observer means that the researcher observed the events happening in the class and made notes on the field note and checklist. The last observation, the researcher interviewed the teacher problems faced by the teacher in teaching writing narrative by using animated film. Next questionnaires the researcher would ask the students to do the questionnaires about students’ responses to the implementation of writing narrative text by using animated film. The data of the study analyzed qualitatively by using descriptive analysis. The first analysis of process was based on the result of checklist, field note, The teacher faced problem in teaching writing narrative text. The last the students’ responses analyzed based on opinion during the implementation of animated film to teach writing narrative text. It got from result of observation sheet, interview guided, and questionnaires. The data of observation sheet are collected by observing teacher’s and students’ activities when animated film is implemented in the teaching writing in the classroom. For the result of interviewed that faced the problem by the teacher, in using animated film. In the end of observation, the researcher interview the teacher dealing with the used of animated film also, the result of the questionnaires described the students’ responses toward the used of animated film as a material in teaching writing narrative text THE FINDINGS OF THE CLASSROOM OBSERVATION The first observation was conducted on January 7th. It was on Tuesday and the class began at 08.05 am until 09.25 a.m. On the first meeting the teacher and researcher entered the class, the students were noisy and most of the students were not in the class, the leader of the class called several students comes to the class. The teacher started the class by greeting them and introduced the researcher to the students. After that the teacher checked the attendance list; there were two students who were absent in that day and the class consisted 32 students. Before teaching learning process started, the teacher asked the students the example of narrative text, the teacher helped the students in order to get the idea of the narrative text; the teacher brainstormed the students and gave the students about a minute to think. Then, the students told their opinion dealing with the example of narrative text. After all the students gave their opinion about example of narrative text, the teacher added the example of narrative text. The teacher stated that brainstorming was applied in the classroom to make the students think more easily in finding out ideas about the material that the teacher gave. Therefore, they could give their opinion as many as possible guided by the example of narrative text. Besides, the question-answer technique was chosen to improve the students’ to gave their opinion of the example of narrative text. before started the material since they had to think fast and speak spontaneously in answering some question that related with the teacher commanded. The teacher used some media to help the teaching and learning process. The first media used in the class was visual media, that were the LCD projector and whiteboard. LCD was the main media since it helped the teacher in showing the materials and read the material directly. The teacher told the students that they were going to learn about tenses that used to tell past activity, the teacher started to explained about simple past tense, However the teacher repeated the explanation in Indonesian to make sure students could understood. Next activity, the teacher told the students the material, the teacher showed some slides and explained about narrative text, The Purpose of Narrative Text and also the generic structure of narrative text, narrative text consists of three parts: orientation, complication, and resolution, and also language feature, then the teacher repeated the material in order that they could understand. Sometimes the teacher mixed language; she used Indonesian, especially in explanation narrative text to the students. To measure the understanding of narrative text to the students, the teacher gave an example of narrative text in her slide, in narrative text there are factual and non factual (imaginary).The examples of factual texts are: someone’s experience, adventure, historical narratives, etc. The examples of non factual (imaginary) texts are : fairytales, fables and moral tales, myths and legends. The teacher gave example of narrative text the title was Timun Mas there are four paragraph in the story of Timun Mas. Timun Mas one of story tells in the past, in Timun Mas story has orientation, complication, and the last is resolution She asked one student to read the first paragraph of story. After the student read the story based on the slide, teacher explained that the first paragraph on story is Orientatation. Teacher asked the student to read the second and third paragraph after that, the teacher explained that the second and third paragraph were Complication. For the last paragraph the teacher read by her and explained for the last paragraph was Resolution. In the first observation the teacher use pre writing activity, means that in pre writing activity consist of pre viewing activity also viewing activity, in pre viewing activity, the teacher gives information about what will be played, the theme of animated film. The teacher asks to the students to keep silent and also gives command about what students should do during the viewing activity. Also in viewing activity, During the viewing activity, the teacher plays animated film twice. The animated video is about 7 minutes. In this activity students should take a note about the important part in the animated film. Then, several minutes before the class was ended. The teacher showed an animated film with the title Malin Kundang, It took ten minutes, Then the teacher played the animated film and repeated the film twice. After watching animated film, the teacher asked to the students some important thing related to the film and made same note about the characters, setting, and conflict which was found in the film. Finally the teacher left the class by giving nice greeting. The second observation was conducted on January 11th. It was on Saturday and the class began at 06.45 am until 08.05 a.m. The class was started in the same greeting and checking the students’ attendance list. All the students were presents in that time. Before started the lesson the teacher checked the students’ understanding in previous meeting by asking a several students about narrative text, the generic structure and language feature of narrative text. Then, the teacher prepared all the instruments, material, media, etc that were needed because they were going to watch animated film again. Then, the teacher started to play two films like in previous meeting, the first film was about Little Red Riding Hood it took eight minutes and replay the film was twice, the second film was about Malin Kundang it took ten minutes in the film and replay the film twice. They had to choose one film to write by using owns words. The teacher remained the students about the generic structure, language feature of narrative text. In narrative text used past activities in simple past tense, the past form of verb, and also the time signal of past tense. The teacher gave a paper to the students’ to write the story based on the film. The class was silent because the student concentrated the animated film. The teacher asked the students to write the information based on that film, The teacher used Bahasa to make students understood the instruction and to stimulate and arouse the students’ activeness. The participation of the students was enthusiastic when they watched the film, but there were two students who felt sleepy when they were watched animated film. While the students were watching film, they took some notes, to get information’s about the characters, setting, conflict, etc. They also tried to get some important point from that film. The teacher used of LCD or white board as visual media were to make the students understand the materials more clearly since they could directly see what was being explained by teacher. And also made the students get an enjoyable atmosphere in learning English. After watching the film and writing the important thing based on the story, the teacher asked the students’ to write whole story based on the information on the film. The teacher let the students to write as they could; the teacher let their students to open their dictionary for finding the correct past form. It seems that the important thing for the teacher is that the students were able to write the story based on the film. The teacher moved around the class and check whether the students got difficulty or not. Before the class was ended the teacher asked the students to submit their work. There were 32 students submitted their works. The teacher did not forget reviewing of the material in that time. For the last meeting the teacher will gave the result of the students’ writing. In the second observation, the teacher in the implementation of animated film in teaching writing narrative use in pre viewing activity, the teacher gives information about what will be played, the theme of animated film. viewing activity, also in during the viewing activity, the teacher plays animated film twice the last whilst writing activities means that the teacher asked the students to compose a narrative text based on the film. Also the teacher gives 30 minute to the students to write a narrative text. The trird observation was conducted on January 18th. It was on Saturday and the class began at 06.45 am until 08.05 am. It was Saturday and it was the last meeting of the observation. When the teacher and the researcher came to the class, one of the students came late and the teacher let the student followed teaching learning process in the class. Then, the teacher greeted and checked students’ attendance list. All students’ were present at the time. The teacher gave the students’ last meeting work. For students’ who got less ability had to revise their task also the teacher prepared the media that would be taught. The teacher explained narrative text and played the film again and discussed the student task on the previous meeting. For the students’ who got excellent ability, they helped the students’ who got poor ability. The teacher gave several times to students’ to revise their writing. Some students did it well, while the rest still needed more attention in using the past form of the verbs. After they finished in writing task, at the time they submitted their works, the teacher corrected and gave score to them. In post writing activity, the teacher collects the students work, then asks some student to present their work in front the class, also the teacher give comments orally. Next activity, the teacher checked students understanding dealing animated film as the media in teaching narrative text by asking a questions in term of narrative. The teacher Also told the students’ to answer the questionnaires that the researcher gave. The questionnaires were about finding the students’ responses toward the implementation of writing narrative text that had been done by the teacher. The researcher interviewed the teacher related with the teaching writing narrative by using animated film. After all questionnaires were submitted, the teacher closed the class with the same way as usual. Finally, the researcher was greatful to all participants for three-day meeting and class over. The Problem Faced by the Teacher in Teaching and Learning Writing Narrative Text by Using Animated Film.This part deals with the second research question which is about the problems faced by the teacher during the implementation of animated film. In the end of observation the researcher interviewed the teacher. In this part, the researcher used interview to know the problems face by the teacher in using animated film.. The question was the problem of teaching narrative text with animated film. There are many problem faced by the teacher using animate film, the first about in teaching writing narrative by using film for the students who sitting in back of the classroom get difficulties to watched animated film so they must move to front sit. Also in given command to the students to keep off and focus to the film need several time to make the class become quiet. The Second was the student difficult to catch the native speaker, because some of them have limited vocabulary, lastly the students difficult to string up grammar when they had to retell the story in writing form The students’ responses was discussed in the third research question. It got from the questionnaires. The first one is about the students’ opinion toward the implementation of animated film in teaching writing narrative text. There were 32 students who filled the questionnaire. During the process of the teaching narrative text, the researcher gave the questionnaire which consist of eight question. a) Yes, b) No, c) Optional based on the given choice from the researcher such as: hard enough, necessary enough, fairly clear, pretty understand, and pretty interesting. CONCLUSION The researcher conducted observation in eighth grades of the junior high school 1 Bangkalan. In junor high school 1 Bangkalan taught English three times in a week. However in implementation of animated film in teaching writing narrative text there were three steps. In the first step, pre-writing activities included of giving instruction, watched animated film, told the student to take note about the important part of the animated film. The second step,whilst-writing, the teacher asked the students to compose narrative writing based on the animated film that had watched, while the teacher let the student to checked dictionary and guidance the students when there were witting. For the last in post writing, the students writing were submitted and checked by the teacher. By watching animated film as media in teaching writing narrative can gains the students motivation, and also their enthusiasm in teaching learning writing narrative text. it could be concluded that techniques applied in the class were more fun and enjoyable. Visual media used were LCD and whiteboard to help the students watched the film in teaching writing narrative also help teacher in students’ listening skill and the last make more fun atmosphere in the class. For the problem faced by the teacher, the teacher made good conditional to overcome the problem by the teacher, although some of students difficult to catch the native speaker, because some of them have limited vocabulary also the students difficult to string up grammar when they had to retell the story in writing form. It can be seen from their result of students writing in narrative text, some of them had excellent very good, Good Average, fair to poor also Very poor. The students were interested by using animated film. It could be seen that almost of the students gets positive responses of this animated film in teaching narrative text. In result of student writing, the result can be concluded that most of students were able to write narrative text. Although some of students faced some problem in using grammar. SUGGESTION Based on the findings of this study, there are several suggestions offered. The suggestions are addressed to the English teachers of junior high school 1 Bangkalan, the teacher should know the students level when delivering material, and the teacher should create an enjoyable condition in teaching narrative by using animated film. Also, the teachers should encourage the students more to make the students accustomed to using English Reviewing at students’ scores is important because it can give feedback. The teacher should use English optimally so that the student will be accustomed to hear that REFERENCES Alkire, S. 2002. Teaching English as a Foreign Language. New York: Longman Inc. Bogdan, R. C. & Biklen, S. K. 1982. Qualitative Research for Education. An Introduction to Theory and Methods. Boston: Allyn & Bacon Inc. Brown, H. D. 2001. Teaching by Principles: An Interactive Approach to Language Pedagogy, Second Edition. New York: Longman Inc. Callahan, J. F. & Clark, L. H. 1982. Teaching in the Middle and Secondary Schools: Planning for Competence (2nd ed.). New York: Macmillan. Carter V. Good.1972. Essentials of Educational Research Methodology and Design Second Edition. London: Prentice-hall International, inc. Cook, V.1996. Second Language Learning and Language Teaching, Second Edition. London: Arnot Hidder Headline Group. Curzon, L.B.1990. Teaching in Further Education: An Outline of Principles and Practice. London: Cassel Education Davies, I. K. 1981. Instructional Techniques. Washington, D.C : McGraw-Hill Departemen Pendidikan dan Kebudayaan Nasional. 1994. Dekrit Menteri Depdikbud Tentang Muatan Lokal Sekolah Dasar. Jakarta: Depdiknas. Depdiknas. 2006. Standar Kompetensi Mata Pelajaran Bahasa Inggris Sekolah Menegah Pertama dan Madrasah Tsanawiyah. Good, C.V. 1972. Essentials of Educational Research Methodology and Design Second Edition. London: Prentice-Hall Intenational, Inc. Grant, N. 1991. Making the Most of Your Textbook. New York: Longman. Hidayatullah. 2006. Using Smallvielle Film Series to Actieve Students to Write Narrative text. Unpublised Thesis:UNESA Heinich, R., Molsenda, M., and Russel, J.D.. 1993. Instructional Media and the New Technology of Instruction. New York: Macmillan Publishing Company. Jacob, L. H,. et.al (1981). Testing ESL Composition: A Practical Approach. Newbury House Publishers, Inc. Rowley, Massachusetts 01969. Rowley. London. Tokyo. Littlewood, W. 1992. Communicative Language Teaching: An Introduction. New York: Cambridge University Press. Livingstone, C. 1983. Role Play in Language Learning. London: Longman Group. Lonergan, j . 1984. Video in Language Teaching. Cambridge : Cambrige University Press. Nunan, D. 1991. Language Teaching Methodology: A Text Book for Teachers. New York: Prentice Hall. O’ Malley, J, Michael and Pierce. 1996. Authentic Assessment for English Language Learners: Practical Approaches for Teachers. Virginia: Addison-Weasley. Orstein, A. C. 1990. Strategies for Effective Teaching. New York: Harper Collins. Sherman, j. 2003 Using Authentic Video in the language Classroom. United Kingdom: Cambrige University Press.